Uji Efektivitas Sponsorship Produk Bearing Racing pada PT. SKF Indonesia Periode 2008 - 2012 - Willy Yanto, Septian; Gurtama Soemapradja, Tomy (Binus Business Review, 2013)
The highest achievement of marketing is sales transaction, so the marketing strategy should have impacts on sales. Promotion in the form of sponsorship has just been conducted by PT. SKF Indonesia since 2010-2011. This study aims to analyze the development of bearing products in PT. SKF Indonesia and to test the effectiveness of promotional strategies in the form of motor racing team sponsorship based on average sales of the bearing racing products data. Anova test results showed that the average sales prior to sponsorship were smaller than the average sales after sponsorship. Thus, sponsorship strategy is efective to raise the average of bearing racing product sales in SKF Indonesia with Î± = 0.05 and 0.01.